2016
DOI: 10.3389/fnagi.2016.00293
|View full text |Cite
|
Sign up to set email alerts
|

Speech Comprehension Difficulties in Chronic Tinnitus and Its Relation to Hyperacusis

Abstract: Objective: Many tinnitus patients complain about difficulties regarding speech comprehension. In spite of the high clinical relevance little is known about underlying mechanisms and predisposing factors. Here, we performed an exploratory investigation in a large sample of tinnitus patients to (1) estimate the prevalence of speech comprehension difficulties among tinnitus patients, to (2) compare subjective reports of speech comprehension difficulties with behavioral measurements in a standardized speech compre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…In animal studies, central hyperactivity has been associated with tinnitus, reduced sound tolerance, and loudness recruitment ( Attias et al, 2005 ; Cai et al, 2009 ; Middleton et al, 2011 ; Heeringa and van Dijk, 2014 ; Kalappa et al, 2014 ). Tinnitus and reduced sound tolerance are associated with impaired speech comprehension in noise ( Vielsmeier et al, 2016 ) and can cause difficulty using amplification devices ( Lindley et al, 2001 ; Formby et al, 2008 ). Hyperactivity in central auditory pathways could affect other aspects of perception such as spectral contrast perception and temporal processing ( Møller, 1972 ; Blackburn and Sachs, 1990 ; Young et al, 1992 ; Doucet et al, 1999 ; McGinley and Oertel, 2006 ; Chen et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies, central hyperactivity has been associated with tinnitus, reduced sound tolerance, and loudness recruitment ( Attias et al, 2005 ; Cai et al, 2009 ; Middleton et al, 2011 ; Heeringa and van Dijk, 2014 ; Kalappa et al, 2014 ). Tinnitus and reduced sound tolerance are associated with impaired speech comprehension in noise ( Vielsmeier et al, 2016 ) and can cause difficulty using amplification devices ( Lindley et al, 2001 ; Formby et al, 2008 ). Hyperactivity in central auditory pathways could affect other aspects of perception such as spectral contrast perception and temporal processing ( Møller, 1972 ; Blackburn and Sachs, 1990 ; Young et al, 1992 ; Doucet et al, 1999 ; McGinley and Oertel, 2006 ; Chen et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…While tinnitus and hyperacusis do not always overlap clinically, the findings by Hébert et al (ibid) support the relevance of identifying a sub-group of patients for whom specific treatments may be beneficial (Dauman and Bouscau-Faure, 2005 ; Schecklmann et al, 2014 ). Vielsmeier and co-authors reported recently that more than 70% of patients with tinnitus ( n = 351) experienced difficulties understanding speech (Vielsmeier et al, 2016 ). While these difficulties were a concern for 40% of the patients when no specific circumstance was considered, 80% acknowledged that speech understanding was a problem in a cocktail party situation, with multiple sources of noise.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some clinical tests, such as those related to speech understanding, may be helpful in characterizing the impact of tinnitus even in those with normal hearing sensitivity. For instance, tinnitus patients report hearing and speech comprehension difficulties (Tyler and Baker 1983;Tyler et al 2014), with such difficulties increasing in adverse listening environments (Vielsmeier et al 2016). As summarized in Table 1, studies focusing on speech recognition ability in noise have demonstrated that tinnitus patients performed poorly on this task, even when they reported having normal hearing sensitivity.…”
Section: Introductionmentioning
confidence: 99%